Strategic Guidelines for Consolidating Smart Schools and the Notion of Happiness - Aranguren Peraza, Gilberto Natividad (2020)
The essay describes the transcendence of Smart Schools and their impact on developing mental states of happiness. Schools are responsible for building social and creative surroundings through faculty and researchers and develop approaches so students can distance themselves from any inappropriate habits from past generations. Schools should also help contribute to various aspects of student life such as: help develop common sense as well as cognitive and social skills, strengthen interactions through cooperative learning and recreational strategies, develop thought  and systematize drills, strive to rebuild teacher-student relationships, connect their schools with external agents, appreciate the value of work and democratize school authority. These efforts all contribute to making schools smarter. It is important to state that schools that operate according to rigid structures either regarding their administration or teaching methodologies do not foster mental states among students that promote creativity and learning.